Fetal midgut volvulus: report of eight cases. (17th April 2016) - Sciarrone, A.; Teruzzi, E.; Pertusio, A.; Bastonero, S.; Errante, G.; Todros, T.; Viora, E.
Abstract: Objective : To evaluate whether prenatal diagnosis of intestinal midgut volvulus (a rare condition due to the small bowel loops twisting) can improve the prognosis of the newborns. Methods : In our Prenatal Diagnosis Center, eight cases of intestinal volvulus observed between 2007 and 2014 were retrospectively considered. Ultrasonographic signs can be direct and specific (whirlpool sign, coffee bean sign) or indirect and non-specific (abdominal mass, dilated bowel loops, pseudocysts, ascites, polyhydramnios). Results : Prenatal diagnosis was performed at 20–34 weeks of gestation. All newborns were exposed to an emergency surgery: the major complication was due to cystic fibrosis. Conclusions : An early suspicion of intestinal volvulus allows the clinician to refer the patient to a tertiary center so to confirm the diagnosis and perform an appropriate follow-up in order to identify the proper time of delivery. The prognosis of the babies with prenatal intestinal volvulus depends on the length of the segment involved, on the level of intestinal obstruction, on the presence of meconium peritonitis and on the gestational age at birth. Our experience, according with the literature, suggests that ascites and absence of abdominal peristalsis are ultrasonographic signs that, in the third trimester of pregnancy, correctly lead to an immediate delivery intervention.